Hepatoid adenocarcinoma: A wolf in hepatocellular carcinoma's clothing. Issue 10 (8th September 2022) - Nguyen, Paul; Hui, Samuel; Robertson, Marcus
Abstract: Hepatoid adenocarcinoma (HAC) is a rare malignancy that may mimic hepatocellular carcinoma (HCC) given its hepatoid histologic appearance and production of alpha fetoprotein. Clinical management and prognosis of HAC varies considerably from HCC. We present two cases of metastatic HAC in a cirrhotic liver diagnosed after biopsy and histopathological evaluation. The cases underscore the importance of recognizing the limitations of diagnostic imaging and pursuing a biopsy where there is diagnostic uncertainty. Abstract : Hepatoid adenocarcinoma is a rare malignancy that may mimic hepatocellular carcinoma, given its hepatoid histologic appearance and production of alpha fetoprotein. We present two cases of metastatic hepatoid adenocarcinoma in a cirrhotic liver diagnosed after biopsy and histopathological evaluation, which illustrate the importance of pursuing a biopsy in cases of diagnostic uncertainty and review by an experienced pathologist.